Incidence and risk factors for herpes simplex virus type 2 seroconversion among pregnant women in Uganda: A prospective study - Nakubulwa, Sarah; Kaye, Dan K.; Bwanga, Freddie; Mbona Tumwesigye, Nazarius; Nakku-Joloba, Edith; Mirembe, Florence M. (The Journal of Infection in Developing Countries, 2016)
Herpes simplex virus type 2 (HSV-2) acquired during pregnancy is associated with adverse outcomes such as perinatal HSV-2 transmission. HSV-2 seroconversion occurs within four weeks of HSV-2 acquisition. There was neither documented incidence nor risk factors for HSV-2 seroconversion during pregnancy in Uganda. The objective of this study was to determine the incidence and risk factors for HSV-2 seroconversion among pregnant women in Mulago Hospital, Uganda. Methodology: A prospective study of 200 consenting HSV-2-negative women between 26 and 28 weeks of gestation was done between November 2013 and October 2014. HSV-2 serostatus was determined using HerpeSelect HSV-2 enzyme-linked immunosorbent assay (ELISA). Interviewer-administered questionnaires were used to collect socio-demographic characteristics and sexual history. Human immunodeficiency virus (HIV) serostatus was obtained from antenatal records. A total of 191 women completed follow-up and repeat HSV-2 serology by 38 weeks. Negative binomial regression analysis was used to estimate risk ratios for risk factors for HSV-2 seroconversion. Results: Of 191 women, 15 (7.9%) seroconverted during pregnancy. Having multiple sexual partners, being in polygamous unions, and having HIV-positive serostatus were found to be risk factors for HSV-2 seroconversion. Conclusions: The incidence of HSV-2 seroconversion during pregnancy in Uganda was high. Multiple sexual partners, polygamy, and HIV-positive serostatus were risk factors for HSV-2 seroconversion during pregnancy. Strengthening health education on the avoidance of multiple sexual partners during pregnancy is paramount in prevention of HSV-2 seroconversion.
Keywords: Herpes simplex virus type 2; Incidence; Seroconversion; Pregnancy; Risk factors